2021
DOI: 10.1101/2021.11.01.466725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intratumoral Delivered Novel Circular mRNA Encoding Cytokines for Immune Modulation and Cancer Therapy

Abstract: The application of mRNA as a novel kind of vaccine has been proved recently, due to the emergence use authorization (EUA) by FDA for the two COVID-19 mRNA vaccines developed by Moderna and BioNTech. Both of the two vaccines are based on canonical linear mRNA, and encapsulated by lipid nanoparticle (LNP). Circular mRNA, which is found to mediate potent and durable protein expression, is an emerging technology recently. Owing to its simplicity of manufacturing and superior performance of protein expression, circ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…In our previous studies, we proved that cmRNA can mediated strong and durable protein expression both in vitro and in vivo. Moreover, our studies demonstrated that cmRNA is sufficient for the expression of various types of proteins (9). Therefore, we prospect that cmRNA is probably an excellent vector to deliver and express BioPROTAC molecules intracellularly.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…In our previous studies, we proved that cmRNA can mediated strong and durable protein expression both in vitro and in vivo. Moreover, our studies demonstrated that cmRNA is sufficient for the expression of various types of proteins (9). Therefore, we prospect that cmRNA is probably an excellent vector to deliver and express BioPROTAC molecules intracellularly.…”
Section: Discussionmentioning
confidence: 88%
“…Since mRNA delivery has been studied extensively, and undergone well-developed (18), we consider that efficient in vivo delivery of cmRNA based RiboPROTAC is highly promising. We have previously shown that direct intratumoral injection of naked cmRNA resulted in durable protein expression in tumor tissues (9). Hence, we used this mouse model to verify RiboPROTAC’s application in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the report from Weesselhoeft et al, the translation initiation sequence, or exactly IRES of Coxsackievirus B3 (CVB3) was identified as the most potent IRES for the direction of circRNA mediated protein expression. In our previous reports, we identified the IRES of Echovirus 29 (E29) and E33 as stronger element to induce protein expression 24 . In the current study, we broadened the screening of IRES in varying strains of virus and attempted to identify better IRES for Clean PIE circRNA.…”
Section: T4td Splicing Site Concealing In Translation Initiation Sequ...mentioning
confidence: 99%